Proteasome inhibition by new dual warhead containing peptido vinyl sulfonyl fluorides. Issue 16 (15th August 2016) - Brouwer, Arwin J.; Herrero Álvarez, Natalia; Ciaffoni, Adriano; van de Langemheen, Helmus; Liskamp, Rob M.J.
Graphical abstract: Abstract: The success of inhibition of the proteasome by formation of covalent bonds is a major victory over the long held-view that this would lead to binding the wrong targets and undoubtedly lead to toxicity. Great challenges are now found in uncovering ensembles of new moieties capable of forming long lasting ties. We have introduced peptido sulfonyl fluorides for this purpose. Tuning the reactivity of this electrophilic trap may be crucial for modulating the biological action. Here we describe incorporation of a vinyl moiety into a peptido sulfonyl fluoride backbone, which should lead to a combined attack of the proteasome active site threonine on the double bond and the sulfonyl fluoride. Although this led to strong proteasome inhibitors, in vitro studies did not unambiguously demonstrate the formation of the proposed seven-membered ring structure. Possibly, formation of a seven-membered covalent adduct with the proteosomal active site threonine can only be achieved within the context of the enzyme. Nevertheless, this dual warhead concept may provide exclusive possibilities for duration and selectivity of proteasome inhibition.